The Dynamics of Social and Cultural Values of Koro in the Contemporary Life of the Gayo People, Aceh Province - Nasution, Oleh: Abdullah Akhyar; Sirojuzilam,; Harahap, R. Hamdani; Tafsin, Ma’ruf (International Journal of Psychosocial Rehabilitation, 2020)
One of the problems of development now is the disappearance of local genetic resources as a source of food. it's caused by genetic engineering and innovation on food mass production. One of animal food source is buffalo. Historical facts showed there are many communities have developed buffalo livestock systems as part of their life. One of them is the Gayo people in Aceh, Indonesia. In Gayo buffalo called Koro. To increase the koro population can be done by understanding the social and cultural values of it in that society. It’s can be used to conservating pattern koro livestock based on the emic view of the Gayo community.This article wrote based on the results of research that is focused on Gayo Lues District, Aceh. Data on this research collected by using observation, interviews and study literature technics. The study begins with the description of koro narratives on various cultural channels such as songs and other cultural instruments. All data is processed using "ongoing analysis" in combination with content analysis on some data.The results showed that koro still has very important social and cultural values. It's just that the Gayo people are also realistic in meeting today's needs, primarily economic needs. Today there is a non synchronize between the values at the idea with the action and artifact level. In the idea level, koro is still considered to be very important socially and culturally, but at the level of actions and artifacts, there are deviations. In case if the government wants to revitalize the role of koro as a socially valued cultural symbol, so a renewal on the traditional buffalo livestock system is needed. It's not only about economically valuable added but also how to use the local wisdom of Gayo people and the values on it contain.